The development of methods to improve performance of the logistics chain within the transport and logistics cluster - Алешинский, Евгений Семенович; Мещеряков, Василий Владимирович; Руденко, Анна Сергеевна (Technology audit and production reserves, 2016)
The problems are irreversibly occurred during the transportation process. It is lead to loss of quantity, quality of the cargo and increase of the transportation time, so that the cargo «hangs» in the turnaround. The main disadvantage is the quality performance of the transport services - quantitative characteristic of one or more consumer properties of services that make up its quality. Transportation quality is measured at the aggregate of characteristics that determine their suitability to meet the needs of consignors and consignees in the corresponding transportations. This disadvantage is associated with low functional performance of transport, such as maneuverability, low speed, ease of reception and delivery of the cargo, closure of the service system, adaptability to customer requirements. The research is focused on the development of measures to improve performance during the transportation process. A process chain analysis on the basis of risk analysis is applied in order to develop these activities. At the same time, a reliable criterion based on the functional parameters of the object is proposed to reduce the risks of action on the logistics chain. Its essence lies in the fact that the criterion shows the degree of reliability of the transport company, thus creating potential and information to determine transportation priorities (quantity / quality). This method can be used to create a database for characteristics of the transport company.